2010
DOI: 10.1007/s00417-010-1406-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravitreal bevacizumab on iris vessels in neovascular glaucoma patients

Abstract: A single intravitreal dose of IVB at 1 mg/0.04 ml to eyes with rubeotic glaucoma reduced the neovascularization in the human iris surface, but could not eliminate completely neovascularization in iris stroma. This finding implies that the prevention of hyphema and fibrin formation based on the slit-lamp examination can not be predicted, even if neovascularization in iris surface seems to be eliminated by a single dose of IVB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 27 publications
2
16
0
1
Order By: Relevance
“…2e), corresponding to some previous reports [23][24][25]. However, vessels did not completely disappear from the iridocorneal angle tissue in our specimens.…”
Section: Discussionsupporting
confidence: 87%
“…2e), corresponding to some previous reports [23][24][25]. However, vessels did not completely disappear from the iridocorneal angle tissue in our specimens.…”
Section: Discussionsupporting
confidence: 87%
“…[5860] There have even been studies reporting NVG regression after treatment with anti-VEGF agents, with or without PRP. [6163] …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it did not decrease the risk of postoperative hyphema. Sugimoto et al [21], using resected irises from NVG patients during trabeculectomy, reported that IVB reduced the neovascularization on the iris surface but could not completely eliminate neovascularization in the iris stroma. They also reported that IVB did not prevent postoperative complications at 1 day after trabeculectomy, including hyphema [21].…”
Section: Discussionmentioning
confidence: 99%
“…Sugimoto et al [21], using resected irises from NVG patients during trabeculectomy, reported that IVB reduced the neovascularization on the iris surface but could not completely eliminate neovascularization in the iris stroma. They also reported that IVB did not prevent postoperative complications at 1 day after trabeculectomy, including hyphema [21]. Takihara et al, performing IVB 1 to 5 days before the trabeculectomy for NVG patients, reported that preoperative IVB did not significantly improve the surgical outcomes, in common with our study [20].…”
Section: Discussionmentioning
confidence: 99%